Mere Observations, fair comment and actual facts: the voice of Rehman Rashid - Roslina Abdul Latif, (Penerbit Universiti Kebangsaan Malaysia, 2019)
In the twilight of British Malaya, Rehman Rashid was born. He grew up in independent Malaysia, as his nation approached the turn of the millennium. As a young journalist in 1981, he had believed it simple to see what was special about Malaysia; it was a multi-racial, multi-cultural, multi-lingual country, what could be clearer than that? Rehman wrote passionately about Malaysia, this country that he loved dearly. Dissected to its constituent parts, Malaysia to him was a hopeless mess of conflicting priorities, mutually unintelligible languages, contradictory cultures and blinkered religions. Politics were divisive, its economy exploitive, its pillars of authority buttressed by an impenetrable scaffolding of draconian laws upheld by a parliament in which dominance seemed to matter far more than debate. He also believed that there was no reason for Malaysia to survive this far but it had. This is what he wrote about in his columns called ‘On Friday’ and his different take on things didn’t quite sit well with his peers or his superiors. He chooses above all else to see it as a testament to resilience and durability, and perhaps a certain steely apathy; to the presence of sufficient numbers of citizens prepared not to die for their country. This is where this paper situates this research, within the journalistic construction of this journalist’s writings.